2021
DOI: 10.3390/antiox10071091
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Antioxidant Properties of Bee-Collected Artichoke (Cynara scolymus) Pollen

Abstract: The current study intended to determine, for the first time, phenolic and fatty acid profile, antioxidant and certain nutritional properties of monofloral bee-collected artichoke (Cynara scolymus) pollen. Based on UHPLC-DAD MS-MS analysis the main phenolics in extractable fraction were different flavonol glycosides (in particular Isorhamnetin-3-O-glucoside, 49.2 mg/kg of dry weight) while ferulic acid was the predominant phenolic compound (39.4 mg/kg of dry weight) in the alkaline hydrolyzable fraction. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 60 publications
5
25
0
Order By: Relevance
“…The obtained results for absorbances were used for determination of % of radical inhibition [45] and after that for determination of IC 50 values expressed as μg/ mL of plant extracts. For determination of total antioxidant capacity (TAC) standard assay based on reduction of phosphomolybdenum reagent was applied [46] while ability of extracts to reduce iron(III) ions was determined with application of standard ferric reducing power (FRP) assay. [46] Results were expressed as mg of ascorbic acid equivalents (AAE) per 1 g of dry weight.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results for absorbances were used for determination of % of radical inhibition [45] and after that for determination of IC 50 values expressed as μg/ mL of plant extracts. For determination of total antioxidant capacity (TAC) standard assay based on reduction of phosphomolybdenum reagent was applied [46] while ability of extracts to reduce iron(III) ions was determined with application of standard ferric reducing power (FRP) assay. [46] Results were expressed as mg of ascorbic acid equivalents (AAE) per 1 g of dry weight.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…For determination of total antioxidant capacity (TAC) standard assay based on reduction of phosphomolybdenum reagent was applied [46] while ability of extracts to reduce iron(III) ions was determined with application of standard ferric reducing power (FRP) assay. [46] Results were expressed as mg of ascorbic acid equivalents (AAE) per 1 g of dry weight.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…[31] Several reports showed that the protective action of one antioxidant could also produce the synergistic antioxidant effect by its sacrificial oxidation. [36,45,46] Synergy has been achieved in a binary mixture of plant extracts, and the antioxidant compounds compositions of honeybee pollen depend on the plant metabolites from a plant selected by honeybees, [1,36] transferring these proprieties to the mixture pollen (Figure 2). The MP2, MP3, MP4, and MP5 have the highest antioxidant capacity value (Figure 2); the highest synergy effect was MP2 and MP3 without a significant difference, both from Brassica rapa L. botanical origin (Figure 1; Table1).…”
Section: Synergy Study In the Mixture Of Pollenmentioning
confidence: 99%
“…[52] The same variability between the results of TEAC and free DPPH radical inhibition was observed in a previous study on bee-collected pollen. [53] However, the botanical origin of honey could exert the highest influence on the antioxidant activity, along with processing, handling and storage of samples. [54] The composition of honey, namely phenolics content was in direct relationship to free radical scavenging.…”
Section: Antioxidant Capacitymentioning
confidence: 99%